Macroeconomic Effects of Tax Rate and Base Changes : Evidence from Fiscal Consolidations - Dabla-Norris, Era.; Lima, Frederico (Washington, D.C. : International Monetary Fund, 2018)
This paper examines the macroeconomic effects of tax changes during fiscal consolidations. We build a new narrative dataset of tax changes during fiscal consolidation years, containing detailed information on the expected revenue impact, motivation, and announcement and implementation dates of nearly 2,500 tax measures across 10 OECD countries. We analyze the macroeconomic impact of tax changes, distinguishing between tax rate and tax base changes, and further separating between changes in personal income, corporate income, and value added tax. Our results suggest that base broadening during fiscal consolidations leads to smaller output and employment declines compared to rate hikes, even when distinguishing between tax types.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles